Autosomal recessive limb-girdle muscular dystrophies in the Czech Republic - Stehlíková, Kristýna; Skálová, Daniela; Zídková, Jana; Mrázová, Lenka; Vondráček, Petr; Mazanec, Radim; Voháňka, Stanislav; Haberlová, Jana; Hermanová, Markéta; Zámečník, Josef; Souček, Ondřej; Ošlejšková, Hana; et al. (BMC neurology, 2014)
BACKGROUND: Autosomal recessive limb-girdle muscular dystrophies (LGMD2) include a number of disorders with heterogeneous etiology that cause predominantly weakness and wasting of the shoulder and pelvic girdle muscles. In this study, we determined the frequency of LGMD subtypes within a cohort of Czech LGMD2 patients using mutational analysis of the CAPN3, FKRP, SGCA, and ANO5 genes. METHODS: PCR-sequencing analysis; sequence capture and targeted resequencing. RESULTS: Mutations of the CAPN3 gene are the most common cause of LGMD2, and mutations in this gene were identified in 71 patients in a set of 218 Czech probands with a suspicion of LGMD2. Totally, we detected 37 different mutations of which 12 have been described only in Czech LGMD2A patients. The mutation c.550delA is the most frequent among our LGMD2A probands and was detected in 47.1% of CAPN3 mutant alleles. The frequency of particular forms of LGMD2 was 32.6% for LGMD2A (71 probands), 4.1% for LGMD2I (9 probands), 2.8% for LGMD2D (6 probands), and 1.4% for LGMD2L (3 probands).Further, we present the first results of a new approach established in the Czech Republic for diagnosis of neuromuscular diseases: sequence capture and targeted resequencing. Using this approach, we identified patients with mutations in the DYSF and SGCB genes. CONCLUSIONS: We characterised a cohort of Czech LGMD2 patients on the basis of mutation analysis of genes associated with the most common forms of LGMD2 in the European population and subsequently compared the occurrence of particular forms of LGMD2 among countries on the basis of our results and published studies.
Keywords: Anoctamins; lidé; Genotype; Pentosyltransferases; Humans; Proteins; kalpain; svalové proteiny; Muscle Proteins; pletencové svalové dystrofie; proteiny; Calpain; anoctaminy; Czech Republic; Muscular Dystrophies, Limb-Girdle; polymerázová řetězová reakce; sarkoglykany; Sarcoglycans; Chloride Channels; Polymerase Chain Reaction; chloridové kanály; Česká republika; genotyp; pentosyltransferasy; mutační analýza DNA; DNA Mutational Analysis